Removal of small-ring polycyclic aromatic hydrocarbons using cow and goat milk iron oxide nanoparticles - Isha Gautam; Harshica Fernando (Green Chemistry Letters and Reviews)
This work reports an environmentally friendly method for removing small-ring polycyclic aromatic hydrocarbons (PAHs) using iron oxide nanoparticles (IONPs) synthesized from pasteurized cow and goat milk and iron salts. IONPs were prepared at room temperature using FeSO4 (2.0 g in 500 mL) and 10.0 mL of milk at pH 12. Results show that IONPs were formed with low crystallinity. The presence of Fe was confirmed through energy-dispersive X-ray spectroscopy results. Transmission electron microscopy and X-ray diffraction data show smaller semi-spherical nanometer-size particles in an aggregated state. The PAH removal process was monitored using a fluorescence spectrometer, and the results showed that the type of iron salt used (Fe2+/Fe3+) in the preparation of IONPs had no significant effect on the removal of model PAHs. However, the ring structure of the PAHs plays a role in the time taken for the removal process. All PAHs were removed from water efficiently with naphthalene, anthracene, and fluorene removal efficiencies of 75%, >90%, and 70%, respectively. The current study shows that IONPs formed using milk have the potential to be used to remove PAHs from water.